Perancangan Aplikasi Pengamanan Pesan E-mail Dengan Metode Kriptografi RSA Berbasis Android Studio - Riadi, Rahadatul ‘Aisy; Safrianti, Ery; Sari, Linna Oktaviana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Communication is the most important part of everyday activities. In the current era, communication can be done in various ways. One of them is through electronic messages (E-mail). E-mail is a means of exchanging information through electronic communication by sending, receiving, changing and storing messages. Using e-mail is more practical than writing and sending letters manually. However, the use of email is also very vulnerable to crimes in electronic communication or the internet. Security and confidentiality issues are an important aspect of messages, data and information. This is related to the importance of messages and information sent and received by interested parties or people, whether the authenticity of the messages and information is still maintained or not. Therefore, security is needed to maintain the authenticity of messages or information from the contents of the e-mail using cryptography. Cryptography is the art and science of encryption that aims to maintain the security and confidentiality of data. In maintaining the confidentiality and security of electronic messages, the RSA (Revest Shamir Adleman) algorithm method is used, so that the confidentiality and security of the data or information can be maintained and RSA has security at the level of difficulty in factoring nonprime numbers. RSA has a key pair, namely a public key and a private key. This research produces an android application that aims to maintain the authenticity of message contents and information sent by means of messages that have been sent can only be read through the application. Messages sent through the application will also enter into Gmail's incoming contacts. But the user cannot read the message from Gmail because the contents of the message are encrypted and can only be read from the application. And users can only send messages to other users of the application.Keywords: Cryptography, RSA, Email, Android, Enkripsi. Deskripsi